English as a Tool for Political Ideology within the Works of George Orwell: A Review - Zaid Fouad Hashim; Sattar Abduljabbar Mohammed; Raneen Muwafaq Fadhil (Universitas Muhammadiyah Sidoarjo, 2026)
This study examines the role of English within global political communication by situating it as more than a neutral linguistic medium. General Background: English has become the dominant international language in diplomacy, media, and transnational interaction, shaping communication patterns worldwide. Specific Background: Its widespread use in political discourse positions it as a carrier of ideological meanings embedded within language structures and usage contexts. Knowledge Gap: However, limited attention has been given to how English operates as an instrument that conveys and reinforces political ideology across different sociopolitical environments. Aims: This research aims to analyze how English functions as a tool for expressing and disseminating political ideology in global discourse. Results: The findings reveal that English is strategically employed to frame narratives, legitimize power structures, and influence perception in political communication, particularly through media and institutional discourse. Novelty: The study highlights the dual role of English as both a communicative medium and an ideological mechanism, emphasizing its embedded political dimensions. Implications: These insights contribute to a deeper understanding of language and power relations, encouraging critical awareness of linguistic choices in global political contexts and supporting further interdisciplinary research in discourse analysis and sociolinguistics. Highlights:• English Operates as a Medium Carrying Ideological Meanings in Political Communication• Linguistic Choices Shape Narratives and Legitimize Authority Structures• Global Discourse Reflects Embedded Power Relations Through Language Use Keywords: English Language, Political Ideology, Global Discourse, Language And Power, Critical Discourse Analysis.